2016
DOI: 10.1038/srep38322
|View full text |Cite
|
Sign up to set email alerts
|

Horses discriminate between facial expressions of conspecifics

Abstract: In humans, facial expressions are rich sources of social information and have an important role in regulating social interactions. However, the extent to which this is true in non-human animals, and particularly in non-primates, remains largely unknown. Therefore we tested whether domestic horses (Equus caballus) could discriminate between facial expressions of their conspecifics captured in different contexts, and whether viewing these expressions elicited functionally relevant reactions. Horses were more lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 59 publications
4
61
0
Order By: Relevance
“…By using an adapted version of the human FACS and life‐size photographs, it was found that, similar to humans, both horses and sheep are able to perceive informative signals (in particular the amount of sclera visible, pupil dilation and the movement of the facial muscles surrounding the eye) to infer emotional states . Interestingly, both species showed adaptive behavioral responses, showing more avoidance for agonistic or stressed expressions compared to neutral ones …”
Section: Emotion Recognition In Nonhuman Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…By using an adapted version of the human FACS and life‐size photographs, it was found that, similar to humans, both horses and sheep are able to perceive informative signals (in particular the amount of sclera visible, pupil dilation and the movement of the facial muscles surrounding the eye) to infer emotional states . Interestingly, both species showed adaptive behavioral responses, showing more avoidance for agonistic or stressed expressions compared to neutral ones …”
Section: Emotion Recognition In Nonhuman Animalsmentioning
confidence: 99%
“…85,86,127 Interestingly, both species showed adaptive behavioral responses, showing more avoidance for agonistic or stressed expressions compared to neutral ones. 85,128 Conspecific emotion recognition abilities have been identified also in domesticated dogs, whose facial displays involve various combinations of movements of the ears, mouth, lips and eye-gaze shifts. 129,130 In particular, combining the exposure to visual and auditory cue Albuquerque et al 83 showed that dogs are able to integrate information from different sensory signals, and to create an internal multimodal representation of categorized emotions, as previously shown in humans and monkeys.…”
Section: Horses Sheep and Dogsmentioning
confidence: 99%
“…When they see a familiar person but hear the voice of someone else (an incongruent situation), they look longer in the direction of the auditory cue than when the person and the voice are congruent 16 . Horses are also capable of detecting emotional expressions on the faces of conspecifics 17 and also of humans including in photographs [18][19][20] . For example in this last study 19 horses which had been presented with a photograph of a person who was either angry or happy adapted their behavior when they were in front of that person in real life.…”
mentioning
confidence: 99%
“…In addition to vocal signals, horses display a wide range of facial expressions [107]. In Wathan et al [108] horses were presented with photographs representing facial expressions of their conspecifics captured in different contexts and their reactions were recorded. Results showed that perception of positive expressions elicited more approaching behaviors (positive valence) and decrease of heart rate (low arousal level) in tested subjects; on the other hand, negative expressions triggered avoidance behaviors (negative valence) and increase of heart rate (high arousal level).…”
Section: Horses' Perception and Communication Of Emotionsmentioning
confidence: 99%